Exploring the landscape of aesthetic pharmacy practice - Kamal Alhallak (Elsevier, 2023)
Background: As pharmacy practice evolves, an increasing number of pharmacists are diversifying into non-traditional roles such as aesthetic procedures. Despite this shift, comprehensive research exploring demographic patterns, motivations, practice settings, and perceived support and barriers among pharmacists in this specialty, particularly in Alberta, Canada, remains scant. Objectives: This study aimed to explore the demographics, experience, practice settings, types of aesthetic services offered, and perceptions of support from the Alberta College of Pharmacy (ACP) among Alberta pharmacists. It also sought to understand the relationship between pharmacists' years of practice and the complexity of the aesthetic services they provide and to assess the impact of contacting the ACP on their perceptions of clarity in the aesthetic injection regulatory framework. Methods: An online survey was disseminated to registered pharmacists in Alberta, gathering data on demographics, experience, practice settings, aesthetic services offered, and perceived barriers and support. Statistical analysis was used to identify significant trends and associations, employing Chi-square, Kendall's tau-c, and Gamma tests. Results: The results showed a significant association between younger age and involvement in aesthetic practice, with a substantial presence in hospital settings. Part-time pharmacists showed stronger involvement, and those with less than five years of experience were more likely to practice aesthetic injections. No statistically significant relationship was found between the years of practice and the complexity of aesthetic services. Clear dissatisfaction was evident regarding the support and communication from the ACP, with contact with the ACP not necessarily resulting in clarity regarding aesthetic practice regulations. Conclusion: The findings suggest that aesthetic practices are becoming a significant part of pharmacy practice, particularly among younger, part-time pharmacists associated with hospital settings. However, this shift calls for improved support, clearer guidelines, and better communication from the ACP, particularly around aesthetic practice regulations.It also emphasizes the need for regulatory bodies to ensure pharmacists are equipped to offer these services safely and effectively, which could be crucial in shaping future policy-making and professional development initiatives.